Security of supply in times of geo-economic fragmentation: Enhancing the external dimension of the EU's raw materials policy - Meike Schulze (Stiftung Wissenschaft und Politik (SWP), 2024)
The recent political consensus on the European Critical Raw Materials Act (CRMA) marks a significant step towards a common raw materials policy within the European Union (EU). Against the backdrop of increasing geopolitical tensions, the EU aims to bolster its "strategic autonomy" within its raw material supply chains. To achieve this goal, it is essential for the EU and its member states to enhance collaboration with mineralrich third countries. The current geopolitical environment will require a concerted effort on the part of the EU with respect to its raw material diplomacy, as only through such effective engagement will the EU be able to diplomatically and programmatically implement raw material partnerships that appeal to third countries.
Keywords: 320; geo-economic fragmentation; EU's raw materials policy; Critical Raw Materials Act (CRMA); Carbon Border Adjustment Mechanism (CBAM); supply chains